Sediment accumulation of Ag, Cu, and Ni through a semi-arid basin as a by-product of the El Triunfo gold mine, Baja California Sur, Mexico. - Sánchez-Martínez, M.A.; Marmolejo-Rodríguez, A.J.; Millán-Gómez, R.; Sánchez-González, A.; Magallanes-Ordóñez, V.R.; Romero-Guadarrama, J.A.; Murillo-Jiménez, J.M. (Journal of Iberian Geology, 2013)
The dispersal of Ag, Cu, and Ni in mine wastes (tailings and ash) was studied from the source of an abandoned gold mine at El Triunfo (Baja California Sur, Mexico) to the adjacent coast of the Pacific Ocean. The highest contamination levels of the studied elements were measured in one sample of the tailings (Ag: 247 mg kg-1; Cu: 1660 mg kg-1; Ni: 111 mg kg-1). Horizontal and vertical distributions of these elements were obtained from the analysis of surface sediments, tailings, a test pit, a sediment core, and dunes. The background levels of these elements were estimated from independent methods. Then, these regional background level calculations were used to determine the normalised enrichment factors (NEFs). Relatively high NEF values (averages of Ag, Cu, and Ni were 24.0, 3.0, and 1.4, respectively) indicated that the area close to the mine waste zone (up to about 18 km from the source area) was moderately to severely polluted. Moderate to null pollution (average NEFs of Ag, Cu, and Ni were 7, 2 and 1, respectively) was interpreted for the area at about 18-49 km from the mine waste zone. Vertical distributions of the elements in sediments of the overbank, the test pit in the mine zone, and the sediment core (at the discharge of the main arroyo Hondo–Las Gallinas–El Carrizal), also revealed enrichment of Ag, Cu, and Ni relative to the surface sediments. This study indicated that historic and contemporary contamination continues to impact the fluvial environment.